CORRELATION OF PREOPERATIVE VOLUME OF ORAL TONGUE SQUAMOUS CELL CARCINOMA (SCC) ON CT SCAN WITH POST-SURGICAL TUMOUR SIZE - Aneeta, FNU; Shoukat, Shaista; Farooq, Faryal; Kumar, Ameet; Kumar, Vinod (Journal of Ayub Medical College Abbottabad, 2021)
Background: Computed tomography (CT) radiological investigation is commonly used worldwide as a reliable method for determining the existence of oral tongue squamous cell carcinoma. This research was carried out to determine the correlation between the pre-surgical results of the CT scan and the size of the post-surgical tumour. Methods: An analytical cross-sectional study was conducted at the radiology department of Jinnah Post Graduate Medical Centre (JPMC), Karachi, Pakistan from May to October 2020. All patients aged 18 years or above of either gender having malignant tumours of the tongue already proven on biopsy were consecutively enrolled. Pre-surgery CT scan images were performed. The preoperative volume on CT scan then correlated with the post-surgical tumour size findings. The tumour thickness level of anterio-posterior (AP), transverse dimension (TS) and craniocaudal (CC) on pre-surgery CT scan and post-surgery tumour size were the outcome variables. Results: Of 84 patients, the mean age of the patients was 48.38 ±11.40 years. There were 56 (66.7%) males and 28 (33.3%) females. A moderate positive correlation of AP tumour size on CT scan was observed with post-surgical AP tumour size (r=0.671, p-value <0.001). Similarly, a moderate positive correlation of TS tumour size was observed with post-operative TS tumour size (r=0.692, p-value <0.001). While, a strong positive correlation of CC tumour size was observed with post-operative surgical tumour size (r=0.787, p-value <0.001). Conclusion: This study has reported a strong positive correlation of tumour thickness level on CT scan with post-surgical findings for determining the oral tongue squamous cell carcinoma.